Current barriers to treatment for wet age-related macular degeneration (wAMD): findings from the wAMD patient and caregiver survey - Varano M; Eter N; Winyard S; Wittrup-Jensen KU; Navarro R; Heraghty J (Clinical Ophthalmology, 2015)
Monica Varano,1 Nicole Eter,2 Steve Winyard,3 Kim U Wittrup-Jensen,4 Rafael Navarro,5 Julie Heraghty6On behalf of the wAMD Patient and Caregiver Survey Committee members1Department of Ophthalmology, Fondazione GB Bietti-IRCCS, Rome, Italy; 2Department of Ophthalmology, University of Münster, Münster, Germany; 3Department of Policy and Campaigns, Royal National Institute of Blind People, London, UK; 4Bayer Pharma AG, Berlin, Germany; 5Instituto de Microcirugía Ocular, Barcelona, Spain; 6Macular Disease Foundation Australia, Sydney, NSW, AustraliaPurpose: A cross-sectional survey to evaluate the current management of wet age-related macular degeneration (wAMD) and to identify barriers to treatment from a patient and caregiver perspective.Methods: An ophthalmologist-devised questionnaire was given to a global cohort of patients who were receiving (or had previously received) antivascular endothelial growth factor injections and to caregivers (paid and unpaid) to evaluate the impact of wAMD on their lives.Results: Responders included 910 patients and 890 caregivers; wAMD was diagnosed in both eyes in 45% of patients, and 64% had been receiving injections for >1 year. Many caregivers were a child/grandchild (47%) or partner (23%) of the patient; only 7% were professional caregivers. Most (73%) patients visited a health care professional within 1 month of experiencing vision changes and 54% began treatment immediately. Most patients and caregivers reported a number of obstacles in managing wAMD, including the treatment itself (35% and 39%, respectively). Sixteen percent of patients also missed a clinic visit.Conclusion: Most patients seek medical assistance promptly for a change in vision; however, about a quarter of them do not. This highlights a lack of awareness surrounding eye health and the impact of a delayed diagnosis. Most patients and caregivers identified a number of obstacles in managing wAMD.Keywords: antivascular endothelial growth factor agents, patient-reported outcomes, wAMD patient and caregiver survey, wet age-related macular degeneration